Factors Influencing HPV-related Infection Preventive Behavioral Intention among Female University Students - Sun Hwa Kim; Mi Hae Sung (Korean Society of Women Health Nursing, 2017)
PURPOSE: The purpose of this study was to identify impacts of HPV-related knowledge, attitude to HPV vaccination, and health beliefs on infection preventive behavioral intention targeting female university students. METHODS: With correlational survey design, subjects of this study were 120 female students at universities located in B metropolitan city and G city. A total sample agreed to participate in the study. Data were analyzed using descriptive statistics, t-test, ANOVA, correlation, and stepwise multiple regression. RESULTS: Attitude to HPV vaccination, experience of smoking, and HPV-related health beliefs were significant factors influencing the HPV-related infection preventive behavioral intention. These factors accounted for 19.0% of the HPV-related infection preventive behavioral intention. CONCLUSION: The most significant factor for HPV infection prevention was the attitude to HPV vaccination. These findings may be useful to develop strategies to improve the HPV infection preventive behavioral intention of the female university students who have a high risk of the HPV infection.